Retributive considerations in parole proceedings - Assy, Rabeea (Criminal justice and behavior, 2015)
In "Looking Beyond Risk in Paroling Denying Prisoners", Dr. Dagan provided a refreshing critical analysis of the role of retributive considerations in parole proceedings. Its main argument is that if we are to make sense of the insistence on an admission of guilt, we cannot discuss parole proceedings merely in terms of prevention and risk. What is actually in play, at least in part, is retribution and moral evaluation. Taking retributive considerations into account enables a better understanding of the importance that admissions assume in parole proceedings and their role as a means of moral repentance and catharsis. In this brief commentary, we discuss Dagan's thesis, offering a few remarks on the relationship between retribution and prevention. We provide some details on the nature of parole proceedings and on the practices that may increase the likelihood of moral and retributive considerations being taken into account contrary to the will of parliament and to the stated principles of parole.